Aplikasi Augmented Reality Sebagai Media Pembelajaran Pengenalan Organ Tubuh Manusia Di Sekolah SDN Uungan Kecamatan Awayan Kabupaten Balangan - Iqbal, Muhammad; Purbiyanto, Eko; Hamid, Abdul (Indonesian Journal of Information Technology and Computing (IMAGING), 2024)
Teaching human anatomy, a crucial subject for elementary students, benefits greatly from innovative educational tools. Augmented Reality (AR) is explored as a means to enhance traditional learning methods by integrating interactive 3D models, audio explanations, and zoom features into an AR application. The objective is to make learning about human organs more engaging and informative. The Waterfall model is employed for system development, including stages such as requirements analysis, system design, implementation, testing, and maintenance. Unity 3D, Blender for 3D modeling, and Vuforia for marker-based AR tracking are utilized in the development process. Results show that the AR application significantly improves students' understanding and retention of anatomical concepts compared to conventional methods. The conclusion underscores AR's effectiveness in overcoming the limitations of traditional learning media by offering a more immersive and interactive learning environment. Future development could expand the application’s educational content and further enhance interactivity, potentially broadening AR's impact in various educational contexts.